Structure and biological activities of metal complexes of flumequine. Issue 23 (17th February 2016) - Tsitsa, Ifigenia; Tarushi, Alketa; Doukoume, Panagiota; Perdih, Franc; de Almeida, Andreia; Papadopoulos, Athanasios; Kalogiannis, Stavros; Casini, Angela; Turel, Iztok; Psomas, George
Abstract : Co(ii )–flumequine complexes were characterized and their biological activity was evaluated in regard to DNA- and albumin-binding and antimicrobial and antiproliferative activity. Abstract : The reaction of CoCl2 ·6H2 O with the quinolone antimicrobial agent flumequine (Hflmq) in the absence or presence of the α-diimines 2, 2′-bipyridine (bipy), 1, 10-phenanthroline (phen) or 2, 2′-bipyridylamine (bipyam) resulted in the formation of four mononuclear complexes which were characterized with physicochemical and spectroscopic techniques. The crystal structures of [Co(flmq)2 (bipy)]·2H2 O, [Co(flmq)2 (phen)]·1.6MeOH·0.4H2 O and [Co(flmq)2 (bipyam)]·H2 O were determined by X-ray crystallography. The interaction of the complexes with calf-thymus DNA (CT DNA) was investigated by UV spectroscopy, viscosity measurements, cyclic voltammetry and competitive studies with ethidium bromide in order to evaluate the possible DNA-binding mode and to calculate the corresponding DNA-binding constants. The binding of the complexes to human or bovine serum albumin was studied by fluorescence emission spectroscopy and the corresponding binding constants were determined. The antimicrobial activity of the Co(ii )–flumequine and the recently reported Cu(ii )–flumequine complexes was tested against four different microorganisms ( Escherichia coli, Xanthomonas campestris, Staphylococcus aureus and Bacillus subtilis ) and was found to be similar to that of free Hflmq. The antiproliferative activity of previously reported complexes [Cu(flmq)(phen)Cl], [Zn(flmq)(phen)Cl] and [Ni(flmq)2 (phen)] against human ovarian (A2780) and lung (A549) cancer cell lines is also reported in comparison to the cobalt analogue, [Co(flmq)(phen)Cl], 3, highlighting important differences among the various complexes which may be due to different uptake and modes of action.